DIOSPYROS LOTUS: MICROPROPAGATION AND ANTIOXIDANT ACTIVITY - Hwang, S.; Ock, H. Boo; Suk, M. Na; Pak, S. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Diospyros lotus is a deciduous tree that is native to the Middle East and south Asia, especially China, Korea, and Japan. It bears edible small fruits in autumn and leaves are used widely in folk medicine for their medicinal properties. A protocol for the date plum (Diospyros lotus) was developed. For shoot proliferation, in vitro nodal and apical explants were cultured on various media containing 0.5-2.0 mg/l BA, kinetin, or TDZ. WPM medium supplemented with 0.5 m/l BA displayed the highest proliferation rate (4-7 shoots per explant). The rooting was optimized using MS medium supplemented with 0.5 mg/l IBA with 3-5 roots after 2 months of culture. The rooted plantlets were successfully acclimatized and transferred to potting mix with 92% survival. Antioxidant properties of in vivo grown tissues were evaluated using various assays. The levels of total phenolics and flavonoids of the leaves extracts were also determined. The alcohol extract of date plum leaves had good phenolic (445. 6 mg/g) and flavonoid (260.9 mg/g) contents, and showed the strong antioxidant and free-radical scavenging activity (scavenged 92.1% of DPPH at 250 ug/ml). Leaf extracts had higher activities of anti-oxidant-related enzymes including superoxide dismutase (SOD; 20.5 U/mg protein), catalase (CAT; 4.9 U/mg protein), and ascorbate peroxidase (APX; 105.8 U/mg protein) than mature seed extracts (SOD, 2.1 U/mg protein; CAT, 74.5 U/mg protein; APX, 3.7 U/mg protein). These results establish the antioxidant potential of date plum, which could be used as natural antioxidant source.